Compatibility of the Relationship of Early Recollections and Life Style with Parent Schemas Obtained Through Adlerian Interviews - CANEL, AZİZE NİLGÜN (EDAM, 2016)
In this study, the Adlerian Interview Form has been used as a semi-structured, in-depth interview method to identify the experiences of six participants regarding Adler's concepts of early recollections and life style. Subsequent to transcribing the obtained information, recollections to be included in the analysis were subjected to the criterion sampling method, and three recollections that met the autobiographical memory qualifications were selected. The selected recollections were investigated through narrative analysis as a qualitative research technique. Structured analysis of the narration in the analysis was carried out using Labov's narrative technique, while the method of thematic analysis was used on the themes. Parent schemas as perceived by the participants were identified with the Young Parenting Inventory (YPI), and similarities between the perceived schemas and their early recollections and life styles were determined within the context of the main themes established during the analyses. Analyses revealed that their early recollections were compatible with their life styles, and the parenting roles expressed in their recollection narratives were similar to the schemas identified in the Young Parenting Inventory.
Keywords: Adler; Early recollections; Life style; Parent schema; Autobiographical memory; Narrative analysis; Thematic analysis; EARLIEST MEMORIES; CHILDHOOD; SCALE; EVENTS